2021
DOI: 10.3390/ijerph18147326
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Smartphone Application Measuring Snoring in Adults—How Smart Is It Actually?

Abstract: About 40% of the adult population is affected by snoring, which is closely related to obstructive sleep apnea (OSA) and can be associated with serious health implications. Commercial smartphone applications (apps) offer the possibility of monitoring snoring at home. However, the number of validation studies addressing snoring apps is limited. The purpose of the present study was to assess the accuracy of recorded snoring using the free version of the app SnoreLab (Reviva Softworks Ltd., London, United Kingdom)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The SnoreLab app provided acceptable accuracy values for the measurement of snoring, with the percentage of total snoring assessed by SnoreLab being highly correlated with the proportion of snoring measured by polygraphy. The best agreement between the two methods was achieved when the sum of the loud and epic snoring rates obtained with the SnoreLab app was compared to the total snoring rate measured with the polygraph 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The SnoreLab app provided acceptable accuracy values for the measurement of snoring, with the percentage of total snoring assessed by SnoreLab being highly correlated with the proportion of snoring measured by polygraphy. The best agreement between the two methods was achieved when the sum of the loud and epic snoring rates obtained with the SnoreLab app was compared to the total snoring rate measured with the polygraph 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown varying accuracies of SnoreLab compared to gold standard polygraphy at different percentages of total snoring. 8 Snoring data accrual was also dependent on the participant to activate the app prior to sleep and participants were able to visualize their nightly snoring metrics. Because of inconsistent app use prior to HNS activation, we used the initial 7 days of app data after implant initiation as the baseline.…”
Section: Limitationsmentioning
confidence: 99%
“…Compared to measurements obtained by polysomnography (PSG) in a sample of 19 patients, SnoreLab provided accurate snoring detection ranging from 63% to 95%. 8 This pilot study aims to measure snoring changes during HNS therapy up-titration and demonstrate the use of a smartphone application, SnoreLab, to measure longitudinal snoring changes. This case series examines the feasibility of using snore sound tracking in association with HNS therapy uptitration and sleep apnea treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Their technology is simple, especially for the apps that have no intention to diagnose or correlate it with OSA severity, as their functions are usually restricted to the use of a microphone. The apps using a microphone as the main sensor appear to perform well in the detection of snoring and provide stable data with overall good accuracy (Camacho et al, 2015; Chiang et al, 2022; Figueras‐Alvarez et al, 2020; Klaus, Stummer, & Ruf, 2021). However, the specificity might be low in a real‐world scenario, as the apps might confound snoring from the bed partner, other respiratory sounds from the user, and background noise with actual snoring sounds from the user (Camacho et al, 2015; Stippig, Hübers, & Emerich, 2015).…”
Section: Introductionmentioning
confidence: 99%